Nonresonant formation of H− near unreconstructed Si(100) surfaces - Obreshkov, Boyan; Thumm, Uwe (My University, 2007)
We calculate ab initio the fraction of outgoing negative hydrogen ions that are normally incident on an unreconstructed Si(100) surface with kinetic energies between 50 and 150eV. The ground-state electronic structure of the surface is derived from a self-consistent screened Thomas–Fermi–von Weizsäcker pseudopotential including Wang-Teter shell structure corrections. Orbitals and energies of the electronic states in this potential are obtained by solving Kohn-Sham equations. The dynamics of the transfer of a single electron during the ion-surface collision is represented within the Newns-Anderson model, including image-charge interactions and electron translation factor. We show that the outgoing H− fraction evolves at large distances from the surface due to nonresonant transitions from the valence band levels of the substrate into the affinity level of H−. In particular, we show that electron capture from dangling-bond surface-state resonances determines the final negative-ion fraction. We find good qualitative agreement with the experimental results of Maazouz et al. [Surf. Sci. 398, 49 (1998)] for the scattering of hydrogen atoms and ions on silicon surfaces, even though our calculations do not include the effects of reconstruction and projectile motion parallel to the surface.